Supportive and palliative care of advanced nonmalignant lung disease - Kreuter, Michael; Herth, Felix (Respiration, 2011)
Supportive and palliative care is an interdisciplinary challenge with the aims of symptom relief and improvement of quality of life in end-stage patients. Main complaints of patients with advanced nonmalignant lung disease are depression and anxiety, dyspnea, pain, and coughing. The discomfort of many physicians, caregivers, and family members with discussions about end-of-life care is one obstacle for the timely initiation of palliative care and the uncertainty of the short-term prognosis in most advanced nonmalignant respiratory diseases. Early dialog about supportive care already at the onset of the patient’s first symptoms and contemporaneous to life-prolonging therapy may overcome these barriers. Furthermore, continuing education for health professionals in palliative care ensures adequate palliative support. Here, we review insights into symptom control and palliative care in patients with advanced nonmalignant respiratory disease.